Climate regulation, energy provisioning and water purification: Quantifying ecosystem service delivery of bioenergy willow grown on riparian buffer zones using life cycle assessment - David Styles; Pål Börjesson; Tina D’Hertefeldt; Klaus Birkhofer; Jens Dauber; Paul Adams; Sopan Patil; Tim Pagella; Lars B. Pettersson; Philip Peck; Céline Vaneeckhaute; Håkan Rosenqvist (Ambio, 2016)

Ecosystem Services from Small Forest Patches in Agricultural Landscapes - Guillaume Decocq; Emilie Andrieu; Jörg Brunet; Olivier Chabrerie; Pieter De Frenne; Pallieter De Smedt; Marc Deconchat; Martin Diekmann; Steffen Ehrmann; Brice Giffard; Elena Gorriz Mifsud; Karin Hansen; et al. (Current Forestry Reports, 2016)

Nitrate leaching from three afforestation chronosequences on former arable land in Denmark - KARIN HANSEN; LARS ROSENQVIST; LARS VESTERDAL; PER GUNDERSEN (Global Change Biology, 2007)
In regions dominated by agricultural activities, nitrogen (N) is recognized as a major pollutant in aquatic environments. In north‐western Europe, afforestation of agricultural land is part of a strategy to improve water quality. In Denmark, former arable land has been afforested during the past 40–50 years. This study evaluated the effect of afforestation of former arable land on nitrate leaching, based on three afforestation chronosequences. Precipitation, canopy throughfall and soil water were collected and soil moisture was monitored at two Danish locations, Vestskoven (nutrient‐rich, medium deposition) and Gejlvang (nutrient‐poor, high deposition). Afforestation was performed using Norway spruce [ Picea abies (Karst.) L.] and common oak ( Quercus robur L.) at Vestskoven and Norway spruce at Gejlvang. The results suggest that afforestation of former arable land initially leads to lower nitrate leaching than that occurring under the former agricultural land use, and largely below the standard of 50 mg NO − 3 L −1 for groundwater to be utilized as drinking water. Nitrate concentrations became almost negligible in forest stands of 5–20 years of age. However, after canopy closure (>20 years) nitrate concentrations below the root zone and nitrate leaching tended to increase. This was attributed to increased N deposition with increasing canopy development and decreased N demand once the most N‐rich biomass compartments had been built up. Nitrate leaching started to increase at a throughfall deposition level of about 10 kg N ha −1 yr −1 . Compared with nutrient‐poor sandy soils, nutrient‐rich clayey soils appeared more vulnerable to disturbance of the N cycle and to increased N deposition, leading to N saturation and enhanced nitrate leaching. In approximately the first 35 years after afforestation, nitrate leaching below the root zone was generally higher below oak than below Norway spruce.